2020
DOI: 10.47162/rjme.61.1.18
|View full text |Cite
|
Sign up to set email alerts
|

Is there a relationship in-between ovarian endometriosis and ovarian cancer? Immunohistochemical profile of four cases with coexisting ovarian endometriosis and cancer

Abstract: Endometriosis (EMs) is a benign disease characterized by the presence of endometrial tissue outside the uterine cavity. EMs associated with ovarian cancer (OC) has a relative low incidence (5% to 10%), sometimes with evidence of a transition stage through atypical EMs (1.6% cases). We have assessed 135 consecutive patients with either EMs or OC and, out of them, our study reports on four cases of ovarian EMs and OC: two cases with endometrioid OC and two cases with high-grade serous OC (HGSOC). Cases with EMs … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 43 publications
(82 reference statements)
0
2
0
1
Order By: Relevance
“… 33 Multivariate analysis showed that the Ki-67 labeling index was an independent prognostic factor for CCC. The Ki67 immunomarker reflects cell proliferation and spreading activity associated with severe adhesion 34 and endometriotic cysts’ size. 31 Some articles have summarized that low tumor proliferation may be a behavior of CCC resistance to chemotherapy.…”
Section: Discussionmentioning
confidence: 99%
“… 33 Multivariate analysis showed that the Ki-67 labeling index was an independent prognostic factor for CCC. The Ki67 immunomarker reflects cell proliferation and spreading activity associated with severe adhesion 34 and endometriotic cysts’ size. 31 Some articles have summarized that low tumor proliferation may be a behavior of CCC resistance to chemotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, there was no other association between mode of delivery and HIV infection in our study, although no HIV transmission was registered in 196 patients from Constanta RC and 119 patients from Craiova RC who underwent elective cesarean section. We believe that elective cesarean section should be reserved to those patients with a higher viral load or those who presented late in delivery without any cART treatment, or with poor adherence at cART [27][28][29][30], considering that caesarean scars could lead to other diseases such asendometriosis [31] in the future, which could causeinfertility, chronic pelvic pain, dysmenorrhea, and dyspareunia [32].…”
Section: Discussionmentioning
confidence: 99%
“…Segundo projeto de Roxana-Cleopatra Penciu et al (2020), buscou-se determinar se há alguma associação entre endometriose ovariana e câncer de ovário concomitantes, assim como determinar se há diferenças entre endometrioses associadas com diferentes tipos morfológicos de câncer de ovário. Para isso, rastrearam-se todos os pacientesno Hospital Emergencial do Condado de Sf.…”
Section: Fonte: Autoresunclassified